Love, Law, and War in Ukraine and Israel/Palestine: Rearticulating Podgórecki’s Place in a Polish Become American Sociological Imagination - Kennedy, Michael D. (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
Adam Podgórecki’s place in American sociology, and my own engagement with his work 30 years ago, begins my contribution to this collection. I turn next to consider how some subsequent scholars have explained his work and his potential, and do some of the same by inviting our translation of intuitive and formal law into an exploration of vernacular and professional articulations of justice and law. I then consider the place of love in the relationship before moving on to examine two epoch-ending crises of our time: Russia’s invasion of Ukraine and the war in Israel/Palestine. I conclude with an observation that Podgórecki and other scholars invite us to rethink how the intuitive and the formal, the vernacular and the professional, senses of justice might be rearticulated. I recommend that South Africa’s intervention at the International Court of Justice might be a transformational moment.